Evaluation of the MDM-score system for screening mitochondrial diabetes mellitus in newly diagnosed diabetes patients: a multi-center cohort study in China - Ma, Fuhui; Zhao, Jing; Chen, Yan; Luo, Yunzhi; Du, Yuxuan; Li, Xia; Xu, Tao; Zhou, Zhiguang; Zhou, Kaixin; Guo, Yanying (Frontiers in Endocrinology, 2024)
ObjectiveTo evaluate the performance of MDM-score system in screening for mitochondrial diabetes mellitus (MDM) with m.3243A>G mutation in newly diagnosed diabetes.MethodsFrom 2015 to 2017, we recruited 5130 newly diagnosed diabetes patients distributed in 46 hospitals in China. Their DNA samples were subjected to targeted sequencing of 37 genes, including the mitochondrial m.3243A>G mutation. Based on this cohort, we analyzed the clinical characteristics of MDM and type 2 diabetes (T2DM), and evaluated the overall efficacy of the MDM-score through ROC curve analysis.ResultsMDM patients were diagnosed at a younger age (P =0.002) than T2DM patients. They also had a higher proportion of females, lower body mass index, lower height, lower weight, lower systolic blood pressure, and lower fasting C-peptide (P < 0.05). Among 48 MDM patients, the m.3243A>G heteroplasmy level was higher in MDM score ≥ 3 than in MDM score < 3 (P = 0.0281). There were 23 cases with MDM-score ≥ 3 in clinical T2DM, with an AUC of 0.612 (95% CI: 0.540-0.683, P <0.001) on ROC curve analysis, yielding sensitivity of 47.9%, specificity of 74.4%, positive predictive value of 1.9%, and negative predictive value of 99.3%. This suggests that almost half of MDM patients can be identified by the MDM score system.ConclusionsThe MDM-score is effective for screening MDM in newly diagnosed clinical T2DM, and some metrics may help to improve its performance in the future, thereby assisting clinicians in identifying suitable patients for genetic testing, and preventing misdiagnosis and mismanagement of MDM patients.